Hierarchical‐dimensional Material: A Co(OH)2 Superstructure with Hybrid Dimensions for Enhanced Water Oxidation. Issue 24 (27th June 2019) - Qi, Jing; Chen, Mingxing; Zhang, Wei; Cao, Rui
Abstract: Herein, we propose the concept of hierarchical‐dimensional materials (HDMs), which are 3D superstructures built by low‐dimensional single‐crystalline substructures. HDMs combine the low‐ and high‐dimensional features and are a new class of promising functional materials toward electrochemical reactions. We reported a hierarchical‐dimensional cobalt hydroxide nanosheet assembly for electrocatalytic water oxidation. The assembling is 1D‐oriented, the substructures are 2D nanosheets, and 3D voids are created in the material. The as‐prepared material achieved superior electrocatalytic activity than isolated substructures. The better performance is associated with the improved mass transport, which is demonstrated by the analysis of kinetic‐controlled currents. This protocol can also be applied in preparing efficient catalysts on the surface of industrial current collectors. The proposed concept of HDMs might open a new area of functional materials in heterogeneous electrocatalysis. Abstract : A touch of the void : The concept of hierarchical‐dimensional materials (HDMs) has been proposed. There are both low‐ and high‐dimensional features in the structure of the material (within one isolated single assembly). We reported a hierarchical‐dimensional cobalt hydroxide nanosheet assembly for electrocatalytic water oxidation. The unusual assembling is 1D‐oriented, the substructures are 2D nanosheets, and 3D voids are created in the material. Hierarchical‐dimensional materials have the advantages of both low‐ and high‐dimensional features for electrocatalysis.